1999
DOI: 10.1063/1.124565
|View full text |Cite
|
Sign up to set email alerts
|

Buried single CdTe/CdMnTe quantum dots realized by focused ion beam lithography

Abstract: Articles you may be interested inFine structure of electronhole complexes in single semimagnetic quantum dots AIP Conf.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Plots of the Curie-Weiss temperature Θ versus Mn content x in percent obtained by analysing the EPR data of 3, 6, and 9 nm Cd 1-x Mn x S particles (left) and 3, 6, and 9 nm Zn 1-x Mn x S particles (right). The solid line is calculated using Equation (5), the dashed and dotted lines are calculated using Equation (8).…”
Section: Magnetic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Plots of the Curie-Weiss temperature Θ versus Mn content x in percent obtained by analysing the EPR data of 3, 6, and 9 nm Cd 1-x Mn x S particles (left) and 3, 6, and 9 nm Zn 1-x Mn x S particles (right). The solid line is calculated using Equation (5), the dashed and dotted lines are calculated using Equation (8).…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…In order to fabricate 0D quantum dots or 1D quantum wires, the conventionally used top-down approach (see Figure 1) is to start with two-dimensional quantum wells and to use a lithographic pattern definition followed by a pattern transfer, usually a subsequent etching procedure [1][2][3][4][5][6][7] or a controlled local diffusion process due to ion-bombardment. [8,9] Such top-down approaches usually only yield magnetic semiconductor nanostructures of good structural and optical quality for lateral sizes larger than about 50 nm. Below this size, fabrication-induced surface damage deteriorates the quality of the structures and has a strong undesired effect on optical and magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The promises of this interaction include optical isolators on the giant Faraday effect [2], spintronics [3], lasers [4], and other device applications of tunable bands and lines observed in bulk crystals, magnetic quantum wells [5][6][7], and dots [8,9]. Device operation at the fundamental absorption edge is of special interest because of the most pronounced dependence of the material optical parameters on the interacting photon energy.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been shown that for quantum wells both the emission energy and the distribution of magnetic impurities can be modified [1,2]. The latter can lead to substantial changes of the magneto-optical properties of magnetically doped quantum well structures.…”
mentioning
confidence: 99%
“…We find that for annealed CdTe QDs the exciton diamagnetic shift is about two times larger that for the as-grown ones, suggesting an increase of the average dot size upon annealing. In the case of CdMnTe QDs the emission lines of individual quantum dots narrow significantly from 3 meV down to 0.25 meV showing that effect of spin fluctuations is much reduced probably due to an increase of the average dot size.1 Introduction Post-growth annealing has been widely used to change the properties of semiconductor quantum structures [1][2][3]. In particular, it has been shown that for quantum wells both the emission energy and the distribution of magnetic impurities can be modified [1,2].…”
mentioning
confidence: 99%